Dampak Firm Size, Return on Equity, Debt to Assets Ratio Terhadap Income Smoothing Oleh Perusahaan Manufaktur - Ernita Marliani Halawa; Ermayanti Sitanggang; Munawarah Munawarah (Journal of Business and Economics Research (JBE), 2020)
The purpose of this research is to test or describe the effect partially or simultaneously, variable firm size, return on equity, debt to assets ratio. This is an explanatory research with a quantitative approach analyze a theary used which to know is accepted or rejection of previous test hypotheses. Sampling was done by using the data method in the form the company’s annual finacial reviews are published by the IDX itself for sample usage. Determination of the sample is applied for observation, namely using multiple linear regression analysis techniques and descriptions used sourced from the interior of the IDX financial statements for 2015-2017. The population of 38 companies multiplied by 3 years is the number observation of 114 sample companies in Manufacturing companies listed on the IDX 2015-2017. Descriptive analysis and inferential analysis can characteristically using two models to analyze the research data test. Ratio the method of describing the classical assumptions and testing hypothesis. To determine which observations are drawn a conclusion the result variable states that variable Y income smoothing is not has an influence on the variable X1 firm size, variable Y income smoothing has no effect on the variable X2 Return on Equity (ROE), variable Y income smoothing has no effect on Debt to Assets Ratio (DAR).